Opening Press Conference at the IMF-World Bank Spring Meetings, April 10, 2014 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, notes that the developing countries will have to grow at a pace stronger than any time in the past 20 years to achieve the goal of ending the extreme poverty by 2030. He talks about the need for growth that is inclusive, creates jobs, and assists the poor directly. He calls for ensuring economic growth in the years ahead that is sustainable and takes us off the destructive path of climate change. He focuses on providing the best services possible in countries by keeping a strong presence in country offices and by providing global solutions to local problems. He is optimistic that countries and their partners will take it on, seize this opportunity and erase this stain of extreme poverty from our collective moral conscience once and for all. He fielded questions about China urbanization, Russo-Ukrainian tensions, Ghana’s dependence on the U.S. market, quality versus quantity of development aid, Middle East prospects, World Bank programs in Egypt, poverty in Paraguay, increased fees for advisory services, use of financial intermediaries, and climate change.